Sustainability indicators for festival tourism: A multi-stakeholder perspective. Issue 3 (4th May 2019) - Liu, Chyong-Ru; Lin, Wei-Rong; Wang, Yao-Chin; Chen, Shan-Pei
ABSTRACT: To assist the assessment of sustainable festival tourism, this study develops sustainability indictors for festival tourism by including perspectives from four stakeholders: tourists, local residents, business owners, and government agencies. Using the Delphi technique, a panel of 15 tourism experts identified evaluation indicators from the literature. The experts reached consensus on 20 indicators: tourists (four indicators), local residents (four indicators), government agencies (six indicators), and business owners (six indicators). An analytic hierarchy process (AHP) was conducted to calculate the relative weight of each indicator. Experts placed the greatest importance on tourists (0.4015) then on local residents (0.3275) followed by governmental agencies (0.1605) and business owners (0.1105) in order.